Identification and Characterization of Antiviral Activity of Synthetic Compounds Against Mayaro Virus - Ana Paula Andreolla; Andrea Cristine Koishi; Alessandra Abel Borges; Larissa Albuquerque de Oliveira; Viviane Guedes de Oliveira; Nerilson Marques Lima; Eloah Pereira Ávila; Pedro Pôssa de Castro; Giovanni Wilson Amarante; Mauro Vieira de Almeida; Juliano Bordignon; Claudia Nunes Duarte dos Santos (Pharmaceuticals)
Background/objectives: In Brazil, the co-circulation of arboviruses—such as dengue, Zika, yellow fever, and Chikungunya viruses—creates a complex epidemiological landscape, drawing attention from health authorities due to high morbidity and mortality rates. Also present in this context is the Mayaro virus (MAYV), a neglected arbovirus, which can also cause severe syndromes and has been expanding beyond its usual endemic areas in northern and central-western Brazil. Epidemiological surveillance measures remain limited, and there are no effective prophylactic strategies or antiviral treatments for this neglected arbovirus. In this study, we evaluated the antiviral activity of commercial and synthetic compounds against MAYV using an image high-throughput screening (iHTS) system. Methods: A total of 52 compounds from an FDA-approved commercial library (Tocriscreen) and 50 other compounds were tested. Results: Seven compounds showed anti-MAYV activity and were non-toxic for the following cell lines: Naringenin, LLA9A, chrysin, and its ester C6. Post-infection treatments with these selected compounds significantly decreased the percentage of infected cells and the release of infectious viral particles in the supernatant. Additionally, anti-MAYV activity of these four selected hits was confirmed using several human cell lines and two different MAYV genotypes. Conclusions: Our results indicate that the iHTS platform is effective for screening anti-MAYV drugs and that four promising compounds can efficiently inhibit MAYV replication in human cell lines. Although in vivo studies are still required to confirm the efficacy of the selected hits, our findings provide a starting point for developing a potential treatment for MAYV infections.